2016
DOI: 10.1039/c6gc02330d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free regioselective tandem synthesis of diversely substituted benzimidazo-fused polyheterocycles in aqueous medium

Abstract: An efficient metal-free approach for the synthesis of benzimidazo-fused polyheterocycles in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The direct transformations of N -propargylamines into pyrroles without a coupling partner have not been much explored. Keeping these challenges in mind and continuation of our ongoing research on base-mediated reactions and N -heterocyclic synthesis, herein, we have demonstrated a base-mediated direct transformation of N -propargylamine into 2,3,5-trisubstituted 1 H -pyrroles under transition-metal-free conditions (Scheme c).…”
mentioning
confidence: 93%
“…The direct transformations of N -propargylamines into pyrroles without a coupling partner have not been much explored. Keeping these challenges in mind and continuation of our ongoing research on base-mediated reactions and N -heterocyclic synthesis, herein, we have demonstrated a base-mediated direct transformation of N -propargylamine into 2,3,5-trisubstituted 1 H -pyrroles under transition-metal-free conditions (Scheme c).…”
mentioning
confidence: 93%
“…Reaction was also studied using AgNO 3 and result of catalyzed reaction was unsatisfactory. They have optimized the reaction and explained that there was no need for catalyst, additive, and toxic solvent (Scheme 19) [38].…”
Section: Green Chemistrymentioning
confidence: 99%
“…The Role of Green Solvents and Catalysts at the Future of Drug Design and of Synthesis http://dx.doi.org/10.5772/intechopen.71018 [38].…”
Section: The Other Solvents As Mentioned In Green Chemistrymentioning
confidence: 99%
“…Verma and co-workers recently described an eco-benign tandem method of preparation of various benzimidazo-fused heterocyclic compounds, namely benzimidazofused benzofuro[3,2-c]pyridines, benzimidazo-fused benzofuro/benzothieno[2,3-c]pyridines, and benzimidazofused benzoindolo[3,2-c]pyridines, by using functionally varied alkynyl aldehydes and o-phenylenediamines as starting materials in aqueous medium under transition-metal-free conditions (Scheme 53). 39 The reaction occurs through a one-pot inter-and intramolecular C-N bond formation via regioselective 6-endo-dig cyclization.…”
Section: Scheme 49 I 2 -Mediated Intramolecular Aryl C-h Amination Ofmentioning
confidence: 99%